A prospective, multicenter, real-world observational study evaluating the impact of tibial runoff on clinical outcomes after endovascular therapy for femoropopliteal lesions: Research protocol - Liu, Yang; Wang, Qiqi; Wu, Ziheng; Fen, Zibo; Guo, Lianrui; Li, Qiang; Fang, Xin; Sang, Hongfei; Dai, Yudi; He, Chunshui; Ye, Meng (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Current evidence indicates endovascular intervention is a safe and effective treatment for arteriosclerosis obliterans of the lower extremity. However, the clinical outcome of endovascular intervention for femoropopliteal lesions has been shown to be affected by the status of tibial runoff. It still remains unclear whether endovascular intervention for the tibial runoff is associated with additional benefits. Methods and analysis: This prospective, multicenter, real-world observational study would be carried out from January 2021 to December 2022 in 8 designated centers across China with an estimated sample size of 1200 patients with severe femoropopliteal disease. The pre-procedural status of tibial runoff will be evaluated with the modified SVS score and categorized as good (SVS <5), compromised (SVS 5-10) or poor (SVS>10). Whether the patient would be treated with endovascular intervention for tibial runoff was determined by the treating vascular surgeons. Patients will be categorized into 6 groups based on the status of the tibial runoff and whether tibial runoff endovascular intervention offered. Patients within various groups would be compared with regard to clinically-driven target lesion revascularization, the primary patency rate of the femoropopliteal artery, change in quality of life, changes of Rutherford category, improvement of the Wound, Ischemia, and Foot Infection Classification, and incidence of major adverse events over 24-months follow-up. The results of this study may provide important information to help vascular surgeons to decide whether the tibial runoff should be endovascularly interventioned and which patient population benefits most from tibial runoff intervention. Ethics and Dissemination: This study is approved by the Medical Ethics Committee of the Affiliated hospital of Chengdu University of Traditional Chinese Medicine (no. 2020KL-078) and will be conducted in accordance with the provisions of the Declaration of Helsinki. The study protocol has been registered at Clinicaltrials.gov (Identifier NCT04675632).